Digital Libraries, Its Theory and Practices. - Liu, Yan Quan (2009)
Thirteen chapters and 47 sections of the book"Digital libraries, its theory and practices" were worked on and the book is ready to send to the publisher. Did a paper that was accepted by the journal Library Hi Tech. Visited China and gave 2 seminars in 2 universities in China.
Keywords: dept.ils; faculty_collection; sabbatical_report

The impact of digital resource and service use on urban residents in new england public Libraries—A survey report - Liu, Yan Quan; Wnuk, Agnes (Public Library Quarterly, 2009)
Today, access to digital information is essential to patrons using public libraries, whether they have contact with computers at home, work or school or whether the public library is their only contact. In order to evaluate and ultimately enhance public library digital resources and services, it is critical for administrators, librarians and digital information architects to recognize the impact their current digital offerings have on users. This study utilizes a survey to gauge the perceptions of patrons who use digital resources and services in six urban New England public libraries as part of ongoing research into digital information access in public libraries in the United States from the perspective of users.
Keywords: Digital divide; Digital libraries; Digital resources; Digital resources services; New England public libraries; Public libraries; Urban libraries; dept.ils; peer-reviewed

Exploiting the social style of patrons to improve their satisfaction with the reference interview - Sisselman, Peggy (Library Review, 2009)
Purpose: The purpose of this paper is to discover whether the social styles of patrons affects their perception (and librarians' perception) of the quality of the reference interview. Also, whether learning to assess social styles of patrons improves perception of the quality of the reference interview. Design/methodology/approach: The researcher observed 24 reference interviews, assessed the social style of each patron using a checklist of behavioral characteristics; both patrons and librarians confidentially filled out a survey to assess the outcome of the reference interview. Findings: It appears that the social style of patrons has some effect on how both librarians and patrons perceive the outcome of the reference interview. There also appears to be a correlation between the librarians' awareness of the social styles of people and the outcome of the reference interview. Practical implications: Literature has not provided any data on how social style theory on the four social styles (analytical, expressive, driver, amiable) could be used to improve the reference interview. Originality/value: Social style theory has been explored in academic settings and in the areas of marketing and sales, but not yet in public libraries. © Emerald Group Publishing Limited.
Keywords: Customer satisfaction; Individual perception; Interpersonal communications; Reference services; Social dynamics; dept.ils